The Rule of Law Case Against Inconsistency and in Favour of Mandatory Civil Legal Process. - Higgins, Andrew Allan (Oxford Journal of Legal Studies)
The traditional private, bipolar model of civil litigation has come under strain in a world of mass production and even mass law. The result is that the courts are deciding the same questions of fact or law in multiple proceedings. Multiplicity causes waste and vexation, creates a risk of inconsistent outcomes and raises concerns about adequacy of representation where a court creates a precedent that will affect the rights of others not before the court. This article argues that multiplicity, and the risk of inconsistency that goes with it, is antithetical to legal process using theoretical analysis, including Rawls's tripartite classification of procedural justice concepts, and doctrinal analysis of the rules of procedure and evidence. It concludes by examining different methods for avoiding inconsistency and argues for the adoption of mandatory legal process for all persons wishing to assert claims or defences that give rise to common questions.